Locating nature : making and unmaking international law - Natarajan, Usha; Dehm, Julia (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
For those troubled by environmental harm on a global scale and its deeply unequal effects, this book explains how international law structures ecological degradation and environmental injustice while claiming to protect the environment. It identifies how central legal concepts such as sovereignty, jurisdiction, territory, development, environment, labour and human rights make inaccurate and unsustainable assumptions about the natural world and systemically reproduce environmental degradation and injustice. To avert socioecological crises, we must not only unpack but radically rework our understandings of nature and its relationship with law. We propose more sustainable and equitable ways to remake law's relationship with nature by drawing on diverse disciplines and sociocultural traditions that have been marginalized within international law. Influenced by Third World Approaches to International Law (TWAIL), postcolonialism and decoloniality, and inspired by Indigenous knowledges, cosmology, mythology and storytelling, this book lays the groundwork for an epistemological shift in the way humans conceptualize the relationship between law and nature.
Locating nature : making and unmaking international law / Usha Natarajan and Julia Dehm -- From classical liberalism to neoliberalism : explaining the contradictions in the international environmental law project -- Reconfiguring environmental governance in the green economy : extraction, stewardship and natural capital -- Appropriating nature : commerce, property and the commodification of nature in the law of nations -- Reflections on a political ecology of sovereignty : engaging international law and 'the map' -- The maps of international law : perceptions of nature in the classification of territory beyond the state -- Denaturalising the concept of territory in international law -- Who do we think we are? -- Human rights in a time of ecological change -- Law, labour and landscape in a just transition -- Three enclosures of international law : commoning premises, processes and aims -- The mythic environment : ecocosmology and narrative remakings of environmental consciousness -- Law and politics of the human/nature : exploring the foundations and institutions of the 'rights of nature' -- Narrating nature : climate imaginaries in international law -- Inter-nation relationships and the natural world as relation -- Conclusion.
Title from publisher's bibliographic system (viewed on 22 Sep 2022).
Keywords: Environmental law, International